1992
DOI: 10.1152/ajpgi.1992.262.6.g1041
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation causes hyperplasia and hypertrophy in smooth muscle of rat small intestine

Abstract: Inflammation of the rat jejunum with Trichinella spiralis causes altered smooth muscle contractility by day 6 postinfection (PI). We investigated the association of structural change in the smooth muscle layers with inflammation. By day 6 PI, smooth muscle area in cross sections of jejunum increased (P less than 0.05) in longitudinal (LM) and circular (CM) muscle layers. Nuclei counting in cross sections showed that cell number increased two- to threefold in CM and LM, and this increase was not reversed on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 0 publications
4
101
0
Order By: Relevance
“…13,22,23 Inflammation may also cause SMC hypertrophy within the GI tract. 24,25 However, the molecular mechanism remains less understood. Our in vivo and in vitro data indicated that under the physiologic stress of partial obstruction, intestinal SMCs may lose expression of SRF and characteristic contractile proteins in favor of a dedifferentiated phenotype capable of proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…13,22,23 Inflammation may also cause SMC hypertrophy within the GI tract. 24,25 However, the molecular mechanism remains less understood. Our in vivo and in vitro data indicated that under the physiologic stress of partial obstruction, intestinal SMCs may lose expression of SRF and characteristic contractile proteins in favor of a dedifferentiated phenotype capable of proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The method of Blennerhassett et al 9 was adapted and used for analyzing the thickness of the muscle layer.…”
Section: Methodsmentioning
confidence: 99%
“…. The number of nuclei and the hypertrophy index in the muscles were calculated as previously described (46). Briefly, the total number of nuclei in muscles was calculated by counting the number of nuclei in muscle layers in a determined area, then multiplying by the surface area (μm immunofluorescence Fetal ileum embedded in optimal cutting temperature solution was cut at a thickness of 4 μm for immunofluorescence staining of GFAP and ZO-1 as previously reported (49).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation-induced thickening of the circular and longitudinal muscle layers could be explained by several mechanisms, including hypertrophy and/or secretion of inflammatory cytokines, which are considered to have mitogenic effects on muscle cells (46,50,62). In line with these reports, muscle thickening after HI in our animal model was accompanied by increased cell numbers and cell proliferation within the muscle layers of the fetal intestine and elevated mRNA levels of IL-1b and IL-17, two proinflammatory cytokines that are known to promote intestinal muscle growth (50).…”
Section: Discussionmentioning
confidence: 99%